Patient safety knowledge, attitude and practice among undergraduate health science students in South West Ethiopia - Mohammed, Tofik; Woldearegay, Emebet; Kedir, Shemsu; Ahmed, Kemal; Getnet, Masrie; Gudina, Esayas Kebede (Frontiers in Public Health, 2023)
Abstract Background: Patient safety is the reduction of the risk of unnecessary harm associated with healthcare to an acceptable minimum. It has been identified as a global priority area where substantial knowledge gaps exist. The level of knowledge, attitude, and practice of the health profession toward patient safety has a great impact on the provision of safe patient care. Despite this, the issue has not been sufficiently addressed in Ethiopia, particularly in the current study area. Objective: The aim of this study was to assess the knowledge, attitudes, practices, and factors associated with patient safety among undergraduate health science students at Jimma University. Methods: An institution-based cross-sectional study design was conducted from May to November 2021. Data were collected from 678 undergraduate health science students using a pretested, structured and self-administered questionnaire. EPI data 3.1 was used for data entry, and SPSS version 25 was used for analysis. A binary logistic regression model was utilized to identify factors associated with knowledge, attitude, and practice and factors associated with patient safety. An adjusted odds ratio with a 95% confidence interval and P value of <0.05 were computed to determine the level of significance. Results: The mean age of the participants was 23.9 (±1.6) years; 429 (63.3%) were male. More than half, 355 (52.4%) of them were medical students, and 263 (38.8%) were in the fourth year of their training. Only 43.2% and 45.4% of the students had good knowledge and positive attitudes toward patient safety, respectively. Moreover, only 19.9% of the students had good practices regarding patient safety. Year of study [AOR =3.75, 95% CI: (2.3; 9.3)], duration on practical attachment [AOR = 2.6, 95% CI: (1.2; 5.9)], and knowledge about patient safety [AOR =2.9, 95% CI: (1.9; 3.4] were associated with better patient safety practices. Conclusion: Less than half of the students had good knowledge and a positive attitude toward patient safety. Moreover, only a few of the students had good practices regarding patient safety. Hence, patient safety courses should be included in the curriculum of health science students.